Intermittent Arc Fault Section Location in Power Distribution Network Using Distributed HFCT Disturbance Monitoring - Li, Lulu; Zhou, Xinyue; Wu, Kongyao; Zhong, Yupeng (Proceedings - International Conference on Harmonics and Quality of Power, 2024)
Intermittent arcs in the distribution network have a random distribution and prominent high-frequency characteristics. This paper proposes innovatively using High-Frequency Current Transformers (HFCTs) installed distributedly in cable networks to capture waveforms of intermittent arc faults. Through real HFCT experiments, the paper validates the effectiveness of HFCT in capturing high-frequency arc waveforms. Building upon experimental sampling results, the paper employs empirical mode decomposition (EMD) and the Teager energy operator (TEO) to decompose the filtered arc transient disturbance waveforms through HFCT, and proposes a method for arc section location based on transient disturbance energy and phase comparison. The method is tested on an IEEE 34-node distribution network, demonstrating that the proposed method can effectively localize intermittent arc faults in underground distribution networks. This paper significantly extends the utility value of HFCTs, providing new insights and monitoring schemes for early fault detection in underground cable networks.